Silicon-on-Insulator Couplers for SDM Transmission - Pita, Julian L. (2022)
We present two CMOS-compatible couplers with record-high efficiency for bridging chips and fibers exploiting spatial division multiplexing. The maximum coupling efficiencies to a few-mode and a 7-core fibers were −3.0 dB and −4.3 dB, respectively.